Student Ratings Offer Useful Input to Teacher Evaluations - Michael Scriven (Practical Assessment, Research, and Evaluation, 1994)
Accessed 95,277 times on https://pareonline.net from November 13, 1999 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: College Faculty; *College Students; Data Collection; *Decision Making; Higher Education; *Instructional Improvement; *Student Evaluation of Teacher Performance; *Teacher Effectiveness; *Validity